2023
DOI: 10.1161/circoutcomes.123.010084
|View full text |Cite
|
Sign up to set email alerts
|

Family Engagement in the Adult Cardiac Intensive Care Unit: A Survey of Family Engagement Practices in the Cardiac Critical Care Trials Network

Abstract: BACKGROUND: Cardiovascular and critical care professional societies recommend incorporating family engagement practices into routine clinical care. However, little is known about current family engagement practices in contemporary cardiac intensive care units (CICUs). METHODS: We implemented a validated 12-item family engagement practice survey among site investigators participating in the Critical Care Cardiology Trials Network, a collaborative network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…26 In existing literature, family members' contribution in the ICU is commonly described as either family participation, 27 family involvement, 2,12 or family engagement. 28 For this study, family engagement is considered the proper term to use, as the researchers understand "engagement" as more proactive than "participation" or "involvement." There is a gap in knowledge about family members' engagement in symptom communication, assessment, and management.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…26 In existing literature, family members' contribution in the ICU is commonly described as either family participation, 27 family involvement, 2,12 or family engagement. 28 For this study, family engagement is considered the proper term to use, as the researchers understand "engagement" as more proactive than "participation" or "involvement." There is a gap in knowledge about family members' engagement in symptom communication, assessment, and management.…”
mentioning
confidence: 99%
“…A review of family members' role in pain management in the ICU concluded that family members were willing and capable of contributing in pain assessment and management, but research on this topic was scarce 26 . In existing literature, family members' contribution in the ICU is commonly described as either family participation, 27 family involvement, 2,12 or family engagement 28 . For this study, family engagement is considered the proper term to use, as the researchers understand “engagement” as more proactive than “participation” or “involvement.” There is a gap in knowledge about family members' engagement in symptom communication, assessment, and management.…”
mentioning
confidence: 99%